2019
DOI: 10.1111/sji.12748
|View full text |Cite
|
Sign up to set email alerts
|

Data‐independent acquisition‐based quantitative proteomic analysis reveals differences in host immune response of peripheral blood mononuclear cells to sepsis

Abstract: This study was aimed to uncover proteins that are differentially expressed in sepsis. Data‐independent acquisition (DIA) was used for analysis to identify differentially expressed proteins in peripheral blood mononuclear cells (PBMCs) of patients. A total of 24 non‐septic intensive care unit (ICU) patients, 11 septic shock patients and 27 patients diagnosed with sepsis were recruited for the mass spectrometry (MS) discovery. PBMCs were isolated from routine blood samples and digested into peptides. A DIA workf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Previous studies have reported that the PLS-DA/OPLS-DA model was used to process multiple protein indicators to effectively predict bacterial infections (Kuusela et al, 2017;Tong et al, 2019). In our study, the PLS-DA/OPLS-DA models showed clear identification ability for bacterial infections in SLE.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies have reported that the PLS-DA/OPLS-DA model was used to process multiple protein indicators to effectively predict bacterial infections (Kuusela et al, 2017;Tong et al, 2019). In our study, the PLS-DA/OPLS-DA models showed clear identification ability for bacterial infections in SLE.…”
Section: Discussionsupporting
confidence: 52%
“…This is an explanation for our observation, that the number of low-density granulocytes co-purifying with the PBMC fraction varies highly between patients. Although some of the studies depicting the problem of contaminating, co-purifying low-density granulocytes have been published a decade ago, it is still common practice today to use density gradient centrifugation for PBMC isolation from patients with sepsis (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). This goes along with a lack of reported information on the isolation purity and identification of the contained cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al. studied PBMCs proteome to uncover biomarkers associated with sepsis and septic shock [18]. Non‐septic intensive care unit (ICU) patients, septic shock patients, and patients with sepsis were enrolled.…”
Section: In‐solution Proteomic Approachesmentioning
confidence: 99%